Dielectrophoretic capture of Escherichia coli and boar sperms using ULSI-fabricated three-dimensional protruding TiN nano-electrode arrays - Lu, Hua-Jung; Liao, I-Hsuan; Lien, Chun-Lung; Shiau, Jeng-Huei; Shen, Ching-Fen; Chou, Kuan-Ru; Cheng, Chao-Min (Frontiers in Bioengineering and Biotechnology, 2024)
In recent years, dielectrophoresis has become widely recognized as a highly suitable method for creating good tools for particle separation, with significant successes achieved in a variety of areas.Expanding upon this, we adopted a semiconductor CMOS process, instead of a MEMS process, which allowed for the following: 1) wire insulation to mitigate Joule heat and prevent thermal fluctuation interference with the dielectrophoretic force; 2) isolation of harmful materials from biological samples, making the chip biocompatible; and, 3) the ability to employ nano-electrodes capable of generating a stronger electric field than conventional electrodes, thus allowing chip capture at lower voltages. Additionally, our chip is scalable, enabling multiplied throughput based on sample processing requirements. These features make our chip more widely applicable and suitable for capturing bacteria and sperm. In this study, we focused on optimizing the parameters of dielectrophoresis and employed 3-D protruding TiN nano-electrode arrays to facilitate the capture of Escherichia coli and boar sperms. The experimental data demonstrates that the capture efficiency of this chip for E. coli was approximately 79.25 ± 2.66%, and the highest capture efficiency for sperms was approximately 39.2 ± 3.9%.